Evaluación constructivista para la mejora del rendimiento académico en Química. Año lectivo 2022 – 2023 - Arias Jiménez, Ana Paula (2023)
This curricular integration research, it is worth the importance of the application of constructivist evaluation techniques in the teaching and learning process. These techniques allow students to acquire significative learning, thus to improve their academic performance, for this, the main objective has been to improve the academic performance of students, through the application of constructivist evaluation techniques for the achievement of significant learning, in the subject of Chemistry of the first year of baccalaureate of “Pio Jaramillo Alvarado” educative unit, academic year 2022 – 2023. In relation to the methodology, the inductive method and qualitative approach were used for the diagnosis of the problem through the different instruments, as well as the proposal of a possible solution. For the nature of the information, the research is classified as Participative Action Research, because the active participation of both students, object of study and researcher, was essential during the intervention proposal work. Since other point of view, it is classified as transversal investigation, due to its duration, it corresponds to a previously definite time. Moreover, it is documental because it is necessary to collect bibliographic information for the diagnosis, support and proposal of the problem, likewise in the contrast of results. For the presentation of results, the information is achieved from the searchers. Finally, it is noticeable that the constructivist evaluation techniques more relevant are: problem resolution, written test, and performance analysis. Such techniques, at the moment of being applied in chemistry subject, provide to the learning construction and as a consequence the improvement of academic performance in students. Keywords: learning evaluation, constructivism, evaluation techniques, significative learning.